Tertullian and “Traditio” - Quasten, Johannes (Traditio, 1944)
There are quite a number of passages in Tertullian's writings which deal with traditio. One of the most important is found in chapters 3 and 4 of De corona. Here Tertullian answers those of his opponents who always demand first “Where is it written?” Being a Jurist he discusses the question whether law must be written to be recognized as such. He points to the law of custom which flows from tradition. He strongly denies that in pleading tradition written authority must be demanded.